Technical losses reduction of electrical distribution system in vientiane capital - Phetlamphanh,V. (2015)
This research is aimed to present technical loss analysis in Vientiane capital. Electricité du Laos (EDL), the state enterprise company that is responsible for transmission and distribution of electricity in Lao People's Democratic Republic (Lao PDR). The purposes of this research studies are technical line losses and reduce power losses of distribution in Vientiane capital by using CYMDIST program as tool for simulation. The considering techniques for reducing losses are following: power factor correction by fixed/switch capacitors or capacitors placement, reconfiguration or switching optimization. The total loss is 8,117.4 kW at peak load of all feeders in substations. The total loss has reduced as following: capacitor placement decreases 2,465.5 kW, reconfiguration or switching optimization decreases 1,381.0 kW. Therefore, the total technical losses of distribution are decreased 3,846.6 kW or 47.38%. © 2012 IEEE.